Delineation of gene expression pattern in rice under Rice tungro virus and green leafhopper infestation - Mangrauthia, Satendra Kumar; Jha, Manish; Agarwal, Surekha; Sailaja, B; Rajeswari, B; Krishnaveni, D (Indian Journal of Plant Protection, 2020)
Rice cultivar Taichung Native 1 (TN1) is susceptible to tungro virus and its insect vector-green leafhopper (GLH). We compared the gene expression profiles of GLH and rice tungro disease (RTD) infested TN1 rice plants. Twelve genes were selected for quantitative PCR to analyze their expression in response to virus and insect vector infestation. Out of 12 genes, 9 genes (PCF2, P450, PT, LRR, SAR, RF2A, RVS1, GOX and CAT) were commonly regulated in GLH and RTD infested plants while 3 genes (PBZ1, PRP, and OsNIF2) showed differential expression. The significance of these genes in GLH-Rice-RTD interaction has been discussed. Very high expression (57.80 fold) of PBZ1 in RTD infected plants suggests important role of this gene in host-virus interaction. Further, gene expression pattern indicates the role of PCF2, RF2A, and PRP in symptom development induced by GLH and RTD. This study is important in understanding the common and differential molecular response of host plant to virus and insect vector by modulating the expression of genes involved in diverse biological processes.